PENGARUH KEDISIPLINAN TERHADAP KEPUASAN KERJA PEGAWAI (STUDI PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG) - Janny Adriani Djari; Firdaus Sitepu (Politeknik Ilmu Pelayaran Semarang, 2017)
The purpose of this study to examine the effect discipline by job satisfaction of employees in Seamanship Polytechnic Semarang. Under these conditions, this study took the title